Antiangiogenic therapy for refractory colorectal cancer: current options and future strategies. (February 2017) - Riechelmann, Rachel; Grothey, Axel
Even though significant improvements in the treatment of colorectal cancer (CRC) have been made in recent years, survival rates for metastatic colorectal cancer (mCRC) are poor. Effective treatment options for metastatic colorectal cancer remain limited, and new therapeutic strategies are desperately needed. Several tyrosine kinase inhibitors (TKIs) and monoclonal antibodies (mAbs) that target angiogenesis, a critical process for facilitating tumor cell growth, invasion, and metastasis, are either approved or in clinical development for the treatment of mCRC. Many of these agents have shown efficacy in mCRC, both as single agents and in combination with standard chemotherapy regimens. However, there is a need for predictive markers of response to identify those patients most likely to benefit from antiangiogenic therapy, and, to date, no markers of this type have been validated in patients. Additionally, because antiangiogenic agents typically cause cytostatic as opposed to cytotoxic antitumor effects, it is important to determine the best strategies for evaluating therapeutic response in mCRC to ensure maximum clinical benefit. In this review, we summarize the efficacy and tolerability of approved and investigational antiangiogenic agents for the treatment of mCRC. We also discuss potential markers of response to antiangiogenic agents and how these markers, along with appropriate endpoint selection, can improve clinical trial design.